Hallux valgus measurements using weight-bearing computed tomography: what changes? - Braza, Samuel; Salomão Barbachan Mansur, Nacime; Mallavarapu, Vineel; Alencar Mendes de Carvalho, Kepler; Dibbern, Kevin; Augusto de Souza Nery, Caio; Laleveé, Matthieu; de César Netto, César (Journal of the Foot & Ankle, 2021)
Objective: To assess whether traditional hallux valgus (HV) measurements obtained with conventional radiography (CR) correspond to those obtained with weight-bearing computed tomography (WBCT). Methods: In this retrospective case-control study, 26 HV feet and 20 control feet were analyzed with CR and WBCT. Hallux valgus angle (HVA), intermetatarsal angle (IMA), interphalangeal angle (IPA), distal metatarsal articular angle (DMAA), sesamoid station (SS), and first metatarsal head shape were measured. Chi-square tests were used to compare hallux valgus and control patients. T-tests were used to compare CR and WBCT. P-values less than 0.05 were considered significant. Results: WBCT was capable of discriminating patients with HV from controls, showing higher mean values for HV patients than controls in HVA (35.29 and 9.02, p < 0.001), IMA (16.01 and 10.01, p < 0.001), and DMAA (18.90 and 4.10, p < 0.001). When comparing the two methods, differences were not significant between CR and WBCT measurements in HVA (-0.84, p = 0.79), IMA (-0.93, p = 0.39), IPA (1.53, p = 0.09), or SS (p = 0.40), but were significant for DMAA (13.43, p < .0001). CR analysis yielded varied metatarsal head shapes, while all WBCT shape classifications were round. Conclusion: Unidimensional HV measurements were similar between WBCT and CR, while more three-dimensional findings were not. CR may be used to assess the axial aspects of HV, but multidimensional aspects of the deformity may not be accurately assessed with plain radiographs. Level of Evidence III; Therapeutic Studies; Retrospective Case-Control Study.